ANALISIS KEBUTUHAN DAN PERILAKU ABK TUNAWICARA DALAM PEMBELAJARAN MATEMATIKA DI SDLB PGRI WONOASIH PROBOLINGGO - Terza Travelancya D.P (UNZAH Genggong, 2022)
This study aims to determine the needs and behavior of speech impaired children in Probolinggo City Schools. This research is important to do to find out how the behavior and needs of speech impaired children in learning. The method in this research is descriptive qualitative research. The subject is 1 speech child, selected by random sampling from 4 speech impaired children. The object of this research is the needs and behavior of speech impaired children in learning at SDLB PGRI Wonoasih, Probolinggo City. Data collection techniques in this study are interviews, observation and documentation. The research instrument used was making questions for interviews, observing direct observations of learning activities in class, and documentation in SDLB. The results showed that the needs of speech impaired children were learning media, vocabulary, and good understanding of the material. The behavior of speech-impaired children is that they like lessons depending on the ease or difficulty of the material that we convey. If the material is easy, speech-impaired children are very enthusiastic in learning and vice versa. Deaf and speech-impaired children can concentrate well in class when learning activities begin. Children with hearing impairment can understand the material well with practice. Children who are deaf and speech impaired have high self-esteem, discipline, a competitive spirit, and can accept defeat. Speech-impaired children enjoy learning basic mathematics.Keywords: Deaf-speech; Behavior; Need